Characteristics of Tight Oil Reservoir Based on Nano-CT - Zhe Liu; Wenke Li; Jiajing Li; Wei Wang; Guang Fu (Advances in Materials Science and Engineering)
Besides biotechnology, nano-CT, the ideal technology, can also be used to observe three-dimensional nanostructures in intact cells as part of research into the characteristics of tight oil characteristics. There are few applications in the process and it is still in the early stage of development, but the advantages shown by 3D nanostructure technology are very strong and have strong applicability. Even in the face of tight oil reservoirs with poor physical properties, rapid decline in oil production after volume fracturing, and low oil recovery, it also shows very strong advantages. In order to promote the study of tight oil characteristics and avoid various problems, this article studies the characteristics of tight oil reservoirs based on nano-CT. The results show that the introduction of nano-CT technology into the study of tight oil reservoir characteristics can meet the market demand of tight oil and increase by 3.54%. It can continuously expand and develop rich oil resources under the condition of protecting geology and reservoirs, providing strong technical support for the next generation of large-scale tight oil storage and efficient growth, and can be used to a certain extent for research. The resulting reservoir characteristics solve the problem of excess resources.